Birth and death processes with absorption - Mourad E. H. Ismail; Jean Letessier; Galliano Valent (International Journal of Mathematics and Mathematical Sciences)
Spectral measures and transition probabilities of birth and death processes with λ0=μ0=0 are obtained as limite when λ0→0+ of the corresponding quantities. In particular the case of finite population is discussed in full detail. Pure birth and death processes are used to derive an inequality for Dirichlet polynomials.